MODÉLISATION ET CONTRÔLE D’UN CARREFOUR ISOLÉ À DEUX VOIES - Samir, Derai; Hadiby Rachida, Ghoul; Hassane, Alla (European Scientific Journal, ESJ, 2014)
Urban traffic is a complex system with heterogeneous nature. Vehicleflow that runs out along the lanes can be considered as a continuous flow. Itsdynamics will be modeled by continuous variables in time. The flow isinterrupted by the traffic lights sequences whose commutation cyclecorresponds to a discrete event system. Whole system is typically a hybriddynamic system. In this paper we propose to model this hybrid system by aD-elementary hybrid Petri Net where evolution of the continuous vehiclesflow (continuous marking of HPN), is interrupted by discrete eventssequence of intersection lights (discrete transitions of T-time PN). Thismodel will be translated in a hybrid automaton, where each vertexcorresponds to a continuous dynamic of vehicles flow. Time intervals oftransitions (guards) represent time intervals of traffic lights sequences. Inorder to guarantee a fluid traffic without congestion, we impose limits(specifications) on the continuous marking of each vertex of the automaton,and we recompute the new guards on transitions so that these Specificationsare always respected. Thus, we determine the traffic lights commutation planwhich ensures the waiting time optimization in intersection lights. As a realstudy case we have chosen an intersection traffic lights at the town center ofANNABA.